2017
DOI: 10.1186/s12933-016-0494-2
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes does not impact the diagnostic performance of contrast-based fractional flow reserve: insights from the CONTRAST study

Abstract: BackgroundAdenosine-free coronary pressure wire metrics have been proposed to test the functional significance of coronary artery lesions, but it is unexplored whether their diagnostic performance might be altered in patients with diabetes.MethodsWe performed a post-hoc analysis of the CONTRAST study, which prospectively enrolled an international cohort of patients undergoing routine fractional flow reserve (FFR) assessment for standard indications. Paired, repeated measurements of all physiology metrics (Pd/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…acute coronary syndrome and stable angina). Given the high level of agreement between the two indices, coupled with existing evidence of their equivalent performance versus FFR (15)(16)(17)(18)(21)(22)(23)27) and cardiac positron emission tomography, (24) this study demonstrates that either resting physiologic index can be selected based on local preference and availability. These results further broaden the application of invasive coronary physiologic assessment when an operator decides not to induce hyperemia.…”
Section: Discussionmentioning
confidence: 73%
“…acute coronary syndrome and stable angina). Given the high level of agreement between the two indices, coupled with existing evidence of their equivalent performance versus FFR (15)(16)(17)(18)(21)(22)(23)27) and cardiac positron emission tomography, (24) this study demonstrates that either resting physiologic index can be selected based on local preference and availability. These results further broaden the application of invasive coronary physiologic assessment when an operator decides not to induce hyperemia.…”
Section: Discussionmentioning
confidence: 73%
“…Thus, the accuracy of functional evaluation methods (i.e., QFR) in diabetics has been questioned [14][15][16] . However, several subgroup studies showed QFR maintains favorable performance in patients with T2DM, then dispelled the suspicion that T2DM may in uence the QFR measurement [17][18][19] . Therefore, using QFR to evaluate coronary function in diabetics seems to be feasible and reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this impaired response to hyperemia has been found even in the absence of atherosclerosis. 24 Microvascular dysfunction has been linked with reduced V/M ratio in a retrospective case-control study by Grover et al 1 that reported significantly lower V/M ratios in patients who met the criteria for microvascular angina as compared to their matched controls. This difference was mainly driven by lower coronary artery volumes.…”
Section: Discussionmentioning
confidence: 99%